The Middleware Architecture of MAFTIA: A Blueprint - Veríssimo, Paulo (2000)
In this paper, we present the middleware architecture of MAFTIA, an ESPRIT project aiming at developing an open architecture for transactional operations on the Internet. The former is a modular and scalable cryptographic group-oriented middleware suite, suitable for supporting reliable multi-party interactions under partial synchrony models, and subject to malicious as well as accidental faults